Les hôpitaux psychiatriques du Rhône entre 1946 et 1960 : de nouvelles maisonnées pour les malades non marié∙es - Mathis Farcy (Genre & Histoire)
After the Second World War, which proved to be a gruesome period for people placed in institutions, French psychiatric hospitals underwent several changes, especially to foster social ties between patients. Based on the individual files of 200 unmarried patients hospitalized in the Rhône between 1946 and 1960, this article studies post-war psychiatric hospitals as households. By reappropriating this concept developed by Florence Weber, the aim is to analyse the ties that patients build with each other and with the hospital staff. Types of cohabitation can be observed, which represent a form of daily kinship for unmarried patients. This social organisation within the walls is sometimes supported by biological and legal kinship, which ensures its existence and permanence. Therefore, we shed light on the family and gender logics (re)played in the hospital context during the second part of the twentieth century.